Do firms learn to create value? The case of alliances - Anand, Bharat N.; Khanna, Tarun (Strategic Management Journal, 2000)
We investigate whether firms learn to manage interfirm alliances as experience accumulates. We use contract-specific experience measures in a data set of over 2000 joint ventures and licensing agreements, and value creation measures derived from the abnormal stock returns surrounding alliance announcements. Learning effects are identified from the effects of unobserved heterogeneity in alliance capabilities. We find evidence of large learning effects in managing joint ventures, but no such evidence for licensing contracts. The effects of learning on value creation are strongest for research joint ventures, and weakest for marketing joint ventures. These results are consistent with the view that learning effects are more important in situations characterized by greater contractual ambiguity. Copyright © 2000 John Wiley & Sons, Ltd.